2019
DOI: 10.1177/2325967119839785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of an MRI-Based Classification System for Operative Versus Nonoperative Management of Ulnar Collateral Ligament Tears: A 2-Year Follow-up Study

Abstract: Background: A recently introduced classification system of medial ulnar collateral ligament (UCL) tears accounting for location and severity has demonstrated high interobserver and intraobserver reliability, but little is known about its clinical utility. Purpose: The primary purpose of this study was to assess the relationship of the magnetic resonance imaging (MRI)–based classification system in predicting which athletes had success with nonoperative versus operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Furthermore, after the authors adjusted for age, tear location, and evidence of chronic changes of the UCL on MRI, they reported that the likelihood of failing nonoperative treatment was 12.40 times higher when players had a distal tear. Similarly, Ramkumar et al 17 reported on 23 baseball players who underwent nonoperative management for UCL tears and found that players with distal tears were more likely to proceed to surgical management than those with proximal tears. 17 Conversely, Ford et al 14 reported on the nonoperative management of 35 incomplete UCL injuries in professional baseball players and evaluated their ability to RTS based on tear location (proximal vs distal).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, after the authors adjusted for age, tear location, and evidence of chronic changes of the UCL on MRI, they reported that the likelihood of failing nonoperative treatment was 12.40 times higher when players had a distal tear. Similarly, Ramkumar et al 17 reported on 23 baseball players who underwent nonoperative management for UCL tears and found that players with distal tears were more likely to proceed to surgical management than those with proximal tears. 17 Conversely, Ford et al 14 reported on the nonoperative management of 35 incomplete UCL injuries in professional baseball players and evaluated their ability to RTS based on tear location (proximal vs distal).…”
Section: Discussionmentioning
confidence: 96%
“…While this is the first study to report on the RTS rate and performance upon RTS after UCLR based on UCL tear location (proximal or distal), several previous studies have evaluated the success of nonoperative treatment based on UCL tear locations. 14,15,17 Frangiamore et al 15 evaluated 32 professional baseball players who underwent initial nonoperative management of UCL injuries and compared the success of nonoperative management based on MRI-diagnosed tear location (proximal vs distal). In the authors' cohort, 82% of players with failed nonoperative management had distal tears, while 81% who were successfully treated nonoperatively had proximal tears.…”
Section: Discussionmentioning
confidence: 99%
“…When the authors adjusted for age, injury grade, injury location, and ligamentous changes, only injury location remained significantly associated with failed nonoperative management. Ramkumar et al [30][31][32] published multiple studies on partial UCL injury, including a series of 35 patients treated operatively as compared with 23 patients treated nonoperatively without crossover. A subgroup analysis of baseball players demonstrated that distal tears were 36 times more likely to fail nonoperative treatment and complete tears were 7 times more likely.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that partial injuries occurring in different anatomic locations may behave differently and that some may be amenable to nonoperative management. 15,16,19,21,[29][30][31][32] Unfortunately, uniform consensus has not yet been achieved regarding what tear locations result in the greatest instability or poorest outcomes with nonsurgical treatment. The purpose of this study was to determine the amount of ulnohumeral joint space gapping measured using stress ultrasound with applied valgus stress that occurs with clinically relevant partial tears of the UCL in a cadaveric model as compared with that of the intact and completely torn states.…”
mentioning
confidence: 99%
“…Nine of the 11 whose treatment failed and who went on to surgery had distal ligament injuries, leading the authors to conclude that distal injuries were less likely to respond adequately to nonoperative treatment compared with proximal ones. In a series of 58 athletes, Rankumar and colleagues 25 recently reported that athletes with distal and complete UCL tears were more likely to experience failure after 3 months of rest and rehabilitation and to undergo subsequent surgery. In contrast, in the Chauhan study already discussed, 9 there was only a nonsignificant tendency for players with proximal lesions to return to play more often.…”
mentioning
confidence: 99%